Dentin Hypersensitivity among the medical and non-medical staff of a Hospital Population - A questionnaire-based survey - SRESHTAA, V SRI; R, DR ABILASHA.; RAMAN, DR PRATHIBA (The journal of contemporary issues in business and government, 2020)
Dentinal hypersensitivity (DH) is a common clinical condition usually associated with exposed dentin surfaces , dental pain which is sharp in character and of short duration, arising from exposed dentin surfaces in response to stimuli, typically thermal, evaporative, tactile, osmotic, chemical or electrical; and which cannot be ascribed to any other dental disease. It can affect patients of any age group and most commonly affects the canines and premolars of both the arches.This study aims to assess the prevalence of dentin hypersensitivity among a hospital population in order to assess the causes, preventive measures and awareness about dentin hypersensitivity among the medical and non-medical professionals in a hospital.There are many factors that cause dentin hypersensitivity including tooth brushing practices, brushing materials, diet and oral hygiene practices. A survey with questionnaires regarding brushing practices ,dietary habits, oral hygiene was distributed among medical and non-medical workers in the hospital. The results show that 44.3% experienced dentin hypersensitivity whereas 55.7% did not experience dentin hypersensitivity.73.2% used moderate pressure while brushing their teeth. A lower prevalence of dentin hypersensitivity was found as the population of the hospital have been practising accurate oral hygiene practices which includes the food habits, brushing pressure and selection of toothpaste.Reduction in prevalence of hypersensitivity is achieved when too hot or too cold, acidic substances come in contact with tooth surface.